PENGUATAN KEPENDUDUKAN DAN PEMBATASAN KEKUASAAN PRESIDEN DALAM PERUBAHAN UUD1945 - A. Rosyid Al Atok (Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2011)
Abstract: The four-time amendments ofthe Constitution 1945 have brought quite big implications in the structures of Indonesian constitutional law It is particularly on the organization of the state institutions dealing with the classes, residences, duties, and mandates of the institutions. Take, for example, the president, Before the amendments, president as the holder of the executive power was judged executive heavy. On the other hand, after the amendments, there is a quite significant power resfiietion. However, there is also a strengthening; the president is chosen directly by the peoples. As the result, he has strong political legitimacy. Here, the power restriction of the president is done through controls of the Parliament. The conhols include the mechanisms ofjudgments and agreements of the Parliament on some authorities that fi,rlly belonged to the president before, On one side, the restriction gives a positive impact in avoiding abuse of power, On the othet side, it also emergesanother problem in the statc running because it looks excessive and not proportional,